New classification of upper jaw fractures: anatomical and surgical considerations - Avello Canisto, Francisco (2008)
Fractures of the bony-face bulk or cranio-maxilla-face take place as a result of severe traumatism. According to localization, they are divided into upper jaw or frontal, middle third and lower jaw or mandibular. The upper jaw fractures are the less frequent of the bony-face bulk, with higher incidence in males and between 20 and 40 years old. Traffic accidents and assaults are the main causes; these fractures may be single-, double-, multiple trace or comminute and in some cases they combine with other type of face or panfacial fractures. Age, sex and cause are the most important factors to determine management. We propose a new comprehensive classification of upper jaw fractures that includes important frontal region anatomical and surgical characteristics, of easy application.